Analisis Data Penjualan di Mobile Cell Menggunakan Triple Exponential Smoothing (TES) - Putra, Arios Wardana; Pakereng, Magdalena A.Ineke (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The increasingly rapid development of digital technology has made the use of cellphones increasingly widespread and used by almost all groups, which makes cellphones one of the basic necessities coupled with accessories where these accessories protect cellphones from damage and make cellphones more attractive. A mobile cell shop is a shop that sells cellphones and their accessories, but over time, sales have gone up and down due to several problems that have occurred. This research uses the Triple Exponential Smoothing method to analyze and forecast sales at Mobile Cell Shops. The results of the research show that the MAPE (Mean Absolute Percentage Error) value obtained for the 3 existing sales items has an accuracy level of 50%, which means the forecasting is good and feasible. This can provide insight into making the right decisions in making sales.